ICD shocks and complications in patients with inherited arrhythmia syndromes. (December 2021) - Siskin, Matthew; Cerrone, Marina; Shokr, Mohamed; Aizer, Anthony; Barbhaiya, Chirag; Dai, Matthew; Bernstein, Scott; Holmes, Douglas; Knotts, Robert; Park, David S.; Spinelli, Michael; Chinitz, Larry A.; et al.
Abstract: Background: There is limited information on the long-term outcomes of ICDs in patients with inherited arrhythmia syndromes. Methods: Prospective registry study of inherited arrhythmia patients with an ICD. Incidence of therapies and complications were measured as 5-year cumulative incidence proportions and analyzed with the Kaplan-Meier method. Incidence was compared by device indication, diagnosis type and device type. Cox-regression analysis was used to identify predictors of appropriate shock and device complication. Results: 123 patients with a mean follow up of 6.4 ± 4.8 years were included. The incidence of first appropriate shock was 56.52% vs 24.44%, p < 0.05 for cardiomyopathy and channelopathy patients, despite similar ejection fraction (61% vs 60%, p = 0.6). The incidence of first inappropriate shock was 13.46% vs 56.25%, p < 0.01 for single vs. multi-lead devices. The incidence of first lead complication was higher for multi-lead vs. single lead devices, 43.75% vs. 17.31%, p = 0.04. Patients with an ICD for secondary prevention were more likely to receive an appropriate shock than those with primary prevention indication (HR 2.21, CI 1.07–4.56, p = 0.03). Multi-lead devices were associated with higher risk of inappropriate shock (HR 3.99, CI 1.27–12.52, p = 0.02), with similar appropriate shock risk compared to single lead devices. In 26.5% of patients with dual chamber devices, atrial sensing or pacing was not utilized. Conclusion: The rate of appropriate therapies and ICD complications in patients with inherited arrhythmia is high, particularly in cardiomyopathies with multi-lead devices. Risk-benefit ratio should be carefully considered when assessing the indication and type of device in this population.